Problem Based Learning Model and Cognitive Style on Science Literacy in Fifth Grade Elementary School Students - Ni Kadek Dewi Anggreni; I Gede Margunayasa; I Nyoman Laba Jayanta (Mimbar Ilmu, 2023)
Education has an important role in improving the quality of life for the younger generation. Quality education can be seen from in education, students should be able to think critically in the context of problem-solving, especially with scientific literacy skills. However, in the learning process in elementary schools, it was found that learning was still teacher-centered and needed more learning models, so the learning patterns used could not develop scientific literacy. This study aimed to analyze the impact of problem-based learning models and cognitive styles on scientific literacy in fifth-grade elementary school students. This type of research is quasi-experimental with a nonequivalent post-test-only control group design. The research population was fifth-grade students. The data collection in the study was carried out using the test method. Data collection instruments were multiple-choice tests for scientific literacy and MFFT tests for students' cognitive styles. The statistical analysis used to test the hypothesis uses two-way Anava and Tukey's tests as a follow-up. The research results from hypotheses I, II, III, and IV show that Ho is rejected and H1 is accepted, thus indicating that the problem-based learning model and cognitive style affect the scientific literacy of class V students. This study implies that the problem-based learning model can be used as a benchmark for improving students' scientific literacy so that in the future, teachers will always improve students' thinking skills and scientific literacy in teaching and dare to make changes in implementing learning.